Exploring the multifaceted role of direct interaction between cancer cells and fibroblasts in cancer progression - Dhungel, Nilu; Dragoi, Ana-Maria (Frontiers in Molecular Biosciences, 2024)
The interaction between the tumor microenvironment (TME) and the cancer cells is a complex and mutually beneficial system that leads to rapid cancer cells proliferation, metastasis, and resistance to therapy. It is now recognized that cancer cells are not isolated, and tumor progression is governed among others, by many components of the TME. The reciprocal cross-talk between cancer cells and their microenvironment can be indirect through the secretion of extracellular matrix (ECM) proteins and paracrine signaling through exosomes, cytokines, and growth factors, or direct by cell-to-cell contact mediated by cell surface receptors and adhesion molecules. Among TME components, cancerassociated fibroblasts (CAFs) are of unique interest. As one of the most abundant components of the TME, CAFs play key roles in the reorganization of the extracellular matrix, facilitating metastasis and chemotherapy evasion. Both direct and indirect roles have been described for CAFs in modulating tumor progression. In this review, we focus on recent advances in understanding the role of direct contact between cancer cells and cancer-associated fibroblasts (CAFs) in driving tumor development and metastasis. We also summarize recent findings on the role of direct contact between cancer cells and CAFs and chemotherapy resistance.